Electrocardiographic changes in patients with dilated cardiomyopathy - Sreeramulu, Vietla; Ravi Kiran, Ch Veerendra; Babu D., Dharnesh; Chandra, T Jaya (International Journal of Medical Research and Review, 2020)
Introduction: Cardiomyopathy is the disease of the heart muscle, which causes deterioration of myocardial functioning. A study was conducted to find electrocardiographic findings in dilated cardiomyopathy. Materials and methods: This was a hospital-based study, conducted in the department of General Medicine, GSL Medical College. Informed written consent was taken from each patient or his/her attendant prior to including in the study. Patients with dilated cardiomyopathy, both gender, all ages. Heart failure based on Framingham criteria, ECHO criteria – LV ejection fraction less than 45%, with left ventricular or biventricular dilatation, with global hypo-contractility were included in the study. ECG and 2 D Echo have been performed on the patients. Framingham criteria were used for the diagnosis of heart failure. Descriptive statistics were presented in the form of mean ± standard deviation and percentages. Results: Total 102 patients were included in the study, with a mean age of 56.3 ±12.5 years, the male-female ratio was 1.9. Tachycardia was 61%, left axis deviation was present 34.3% and right axis deviation in 8.8%. Left ventricular end-diastolic and systolic diameters were elevated in most of the patients. Conclusion: With these findings, it can be concluded severe LV systolic dysfunction is very common among dilated cardiomyopathy patients.